Functional characterization of mutants affected in the carbonic anhydrase domain of the respiratory complex I in Arabidopsis thaliana - Soto, Débora (2015)
The NADH–ubiquinone oxidoreductase complex (complex I) (EC 1.6.5.3) is the main entrance site of electrons into the respiratory chain. In a variety of eukaryotic organisms, except animals and fungi (Opisthokonta), it contains an extra domain comprising trimers of putative γ–carbonic anhydrases, named the CA domain, which has been proposed to be essential for assembly of complex I. However, its physiological role in plants is not fully understood. Here, we report that Arabidopsis mutants defective in two CA subunits show an altered photorespiratory phenotype. Mutants grown in ambient air show growth retardation compared to wild–type plants, a feature that is reversed by cultivating plants in a high-CO2 atmosphere. Moreover, under photorespiratory conditions, carbon assimilation is diminished and glycine accumulates, suggesting an imbalance with respect to photorespiration. Additionally, transcript levels of specific CA subunits are reduced in plants grown under non-photorespiratory conditions. Taken together, these results suggest that the CA domain of plant complex I contributes to sustaining efficient photosynthesis under ambient (photorespiratory) conditions.